Results of a questionnaire survey regarding the current status of near-miss/incident/accident reporting in the Saiseikai Clinical Laboratory and efforts to increase the number of reports - TOMITA, Ayako; MOMOTA, Hiroshi; SEKIYA, Koichi (Japanese Journal of Medical Technology, 2025)
Currently, there have been many reports that activating incident and accident reporting activities are important initiative for improving medical safety in clinical scene. However, there are few reports on the number of incidents and accidents that occur in association with the work of clinical laboratory technicians in Japan and overseas. Therefore, we conducted a questionnaire survey on the incident and accident reporting activities at 76 nationwide Saiseikai medical facilities that have clinical laboratories, as well as facilitating activities to increase reporting and the action process against the incidents/accidents. We received responses from 71 (93%) out of 76 facilities. The maximum total number of near misses/incidents/accidents reported was 536, and the minimum was 0. The maximum number of cases reported per technician was 32.3. Many activities were made to increase the number of reports, including promotional activities of reporting, sharing report content, establishing a system for easy reporting, and setting targets for the number of reports. The most common action process against the incident/accident report were: alerting related department staff, changing procedures/work manuals, improving the work environment related to the incident, alerting those who carried out the incident, and revision of educational instruction related to the incident. A positive correlation was found between the number of incident reports and the number of near misses. Although there was no relationship between activities to increase the number of reports and the number of reports, association was found between the number of incident report and the number of actions against incident report. It was thought that improvement actions against incident report had a positive impact on clinical practice and led to an increase in the number of incident reports.